Initial evaluation of the outpatient reference and counter-reference system (ORCR) of DIRIS Lima Norte from maternal-child centers - Llanos Zavalaga, Luis Fernando (2021)
Starting in July 2018 the ORCR was implemented in the IPRESS-DIRIS Lima Norte using the REFCON instrument that includes five processes, three of which occur in the IPRESS of destiny. Objective: To characterize the references of IPRESS I-4 whose destiny were DIRIS Lima Norte and time to appointment of the encounters. Methods: A cross- sectional study was carried-out from May to October 2019 including seven IPRESS I-4. References by age, sex and specialty were analyzed as well as time to appointment. Statistics for means and proportions were calculated using Stata v.16. Results: A total of 19,951 references from seven IPRESS were included in the analysis. The most common age group was 30-59 years (39.22%): women accounted for 67.04%. We excluded from the final analysis 2,714 references for not having information on time to appointment. Only 23.14% of referrals were accepted in less than 24 hours. Half of patients had to wait between 80-85 days to have an appointment. Only 110 counter-references were reported, 43.6% went to Juan Pablo II. Conclusions: We observed a clearly inefficient system with long delays in making appointments and high rate of referral rejections, these findings are the result of lack of regulation, lack of manpower and poor training of the existing personnel.